Psychometric properties of the Lithuanian version of The Impact of Event Scale–Revised (IES-R) - Kazlauskas, Evaldas; Gailienė, Danutė; Domanskaitė-Gota, Vėjūnė; Trofimova, Jelena (Psichologija, 2006)
Objective: The impact of Event Scale–Revised is widely used self-report measure for assessment of PTSD symptoms after a variety of traumatic events. The aim of this study was to examined the psychometric properties of the Lithuanian version of the Impact of Event Scale–Revised.Method: A non-clinical population sample of 406 young adults participated in the study. All participants were exposed to at least one life-time traumatic event meeting A criteria of PTSD according to DSM-IV. Traumatic experiences were assessed using the list of life-time traumatic experiences.Results: The Lithuanian version of Impact of Event Scale–Revised has a good internal consistency. The coefficient alpha for the instrusion subscale was .88, for avoidance subscale alpha .82, and for hyperarousal subscale alpha .85. The Coefficient alpha for the total of Impact of Event Scale–Revised was .93. Subscale intercorrelations were: Intrusion with Avoidance r = .62, Intrusion with Hyperarousal r = .79, and Avoidance with Hyperarousal r = .60. A series of factor principal component analysis using varimax rotation with forced two-, three- and four- factor solutions was undertaken. The two-factor solution explained 49.1% of variance – comprising two gactors Instruction (including Hyperarousal) and Avoidance. The three-factor solution accounted for 54.8% of the variance consistent with three symptom criteria of PTSD: Intrusion, Hyperarousal and Avoidance. Items 2, 12 and 20 loaded on improper factors; item 7 did not load on any of the factors. The four-factor solution explained 59.5% of the variance, yielding four factors: Hyperarausal, Avoidance, Intrusion and Numbing.Conclusions: The Lithuanian version of Impact of Event Scale–Revised was found to have satisfactory psychometric properties. We conclude that the new self-report means of post-traumatic stress is adapted for useon Lithuanian population. Issues concerning norms of Impact of Event Scale–Revised and the limitations of the present study are discussed.
Keywords: post-traumatic stress; assessment methods; Impact of Event Scale-Revised